2004
DOI: 10.1128/mcb.24.11.4613-4626.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial AKAP121 Binds and Targets Protein Tyrosine Phosphatase D1, a Novel Positive Regulator of src Signaling

Abstract: A-kinase anchor protein 121 (AKAP121) and its spliced isoform AKAP84 anchor protein kinase A (PKA) to the outer membrane of mitochondria, focusing and enhancing cyclic AMP signal transduction to the organelle. We find that AKAP121/84 also binds PTPD1, a src-associated protein tyrosine phosphatase. A signaling complex containing AKAP121, PKA, PTPD1, and src is assembled in vivo. PTPD1 activates src tyrosine kinase and increases the magnitude and duration of epidermal growth factor (EGF) signaling. EGF receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
115
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 52 publications
(93 reference statements)
3
115
0
Order By: Relevance
“…8, 9, 13 and the present work) ruled out the possibility that they were washed out. However, recent observations indicate that the protein kinase A anchor protein AKAP121 associates with Src and another tyrosine phosphatase, PTP-1D, on the outer membrane of mitochondria in a human embryonic kidney cell line, HEK293, in response to epidermal growth factor (14,15). The authors proposed that Src translocated inside the mitochondria to regulate tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8, 9, 13 and the present work) ruled out the possibility that they were washed out. However, recent observations indicate that the protein kinase A anchor protein AKAP121 associates with Src and another tyrosine phosphatase, PTP-1D, on the outer membrane of mitochondria in a human embryonic kidney cell line, HEK293, in response to epidermal growth factor (14,15). The authors proposed that Src translocated inside the mitochondria to regulate tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Low Src levels or compensation by other tyrosine kinases in mitochondria from mouse muscle were deduced from studies showing no change in complex IV enzymatic activity in Src Ϫ/Ϫ mice, whereas activity was reduced in liver and kidney mitochondria (13). Other reports evoked the possibility that Src translocated within mitochondria in a human kidney cell line (14,15). Therefore, this tissue-specific distribution of mitochondrial kinases and phosphatases could be correlated to functional tissue differences.…”
mentioning
confidence: 99%
“…HA epitope was placed at the extreme NH 2 terminus of PTPD1 by PCR (22). The HAtagged PTPD1 mutants were generated by PCR using the following primers: PTPD1 ⌬1-581 forward, 5Ј-cggggtaccGTCCCG-CCACCTTTACATCAGC (KpnI in lowercase type); reverse, 5Ј-tgctctagaGCAGATGAGCCTGGAGCTTTTCAG (XbaI in lowercase type); PTPD1 ⌬1-325 forward, 5Ј-ggggtaccaTCTTCA-AGGATGTCTCTGCCT (KpnI in lowercase type).…”
Section: Methodsmentioning
confidence: 99%
“…The PTPD1-Src-AKAP121 complex is required for efficient maintenance of mitochondrial membrane potential and ATP oxidative synthesis. When not in complex with AKAP121, PTPD1 directs EGF-Src signaling to the nucleus, activating ERK1/2-and Elk1-dependent gene transcription (22)(23)(24).…”
mentioning
confidence: 99%
“…However, central for PKA-mediated phosphorylation under physiological conditions are protein kinase A-anchoring proteins (AKAPs), which localize PKA to cellular compartments in close proximity to its targets (44); S-AKAP84 and AKAP121 have been shown to mediate localization of PKA to the outer side of the outer mitochondrial membrane and to be crucial for cAMP-dependent signaling to the mitochondria (45)(46)(47). Also, in this study we found that incubation of isolated mitochondria with cAMP did not change COX activity.…”
Section: Fig 2 Nano-liquid Chromatography/electrospray Ionization/ mentioning
confidence: 99%